2015
DOI: 10.1093/heapol/czv008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of essential medicines programme on rational use of medicines in China

Abstract: China's NEMP is effective in promoting rational use of medicines, and the effect is greater in public institutions than in private institutions. However, the irrational use is still high, pointing to the need for further reforms to tackle the underlying causes, such as clinical guidelines and patient education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…There was a slight increase (2%) in the use of injections for the patients with bronchitis. A lack of proper compensation mechanism is often blamed for the shortage of achievements of China’s National Essential Medicines Program (NEMP)3334. When the 15% markup policy for prescribed medicines was abandoned as part of the NEMP, health care providers had to shift their attention to services that could make up the loss (because of the shortage of government funding)35.…”
Section: Discussionmentioning
confidence: 99%
“…There was a slight increase (2%) in the use of injections for the patients with bronchitis. A lack of proper compensation mechanism is often blamed for the shortage of achievements of China’s National Essential Medicines Program (NEMP)3334. When the 15% markup policy for prescribed medicines was abandoned as part of the NEMP, health care providers had to shift their attention to services that could make up the loss (because of the shortage of government funding)35.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in research conclusions may be due to the use of data from different regions, research period or study design. But overall, these findings have demonstrated that the NEMP interventions are effective: the availability of essential medicines had improved,56 57 but remains at a low level58 59 and had a problem of regional inequity60; drug prices were reduced significantly,57 61–63 and the affordability of essential medicines has improved57 59 60; and the rational use of medicine has effectively improved, but remained poor 56 64–67. In the subjective questionnaire surveys, patients were satisfied with the price and quality of essential medicines 68.…”
Section: Coverage Of Health Servicesmentioning
confidence: 97%
“…[ 46 ] Gong et al . [ 47 ] note that despite improvements in rational medicine use after implementing China's national essential medicines programme, irrational medicine use was still high and called for, among other interventions, review of clinical guidelines which could be one of the underlying causes. An initiative of Medicines Utilization Research in Africa (MURIA) is a great development to stimulate research and act on recommendations for improving rational medicine use.…”
Section: Discussionmentioning
confidence: 99%